2013
DOI: 10.9790/3021-03930109
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Analysis of a Reinforced Concrete Building by Response Spectrum Method

Abstract: Seismic analysis of a multi-story RC frame in Khartoum city was analyzed under moderate earthquake loads as an application of seismic hazard,and in accordance with the seismic provisions proposed for Sudan[1]to investigate the performance of existing buildings if exposed to seismic loads. The frame was analyzed using the response spectrum method to calculate the seismic displacements and stresses.The results obtained, clearly, showthat the nodal displacements caused drifts in excess of approximately 2 to 3 tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The study makes use of the well-known civil engineering application STAAD-PRO to design multi-story buildings and calculate wind and seismic load. Also, they compare the results of calculations made manually and those made using STAAD-Pro when applying an earthquake load to a structure using the seismic coefficient A E. Hassaballa (2013) [7]"Seismic analysis of a multi-story RC frame in Khartoum city was analyzed under moderate earthquake loads as an application of seismic hazard and in accordance with the seismic provisions proposed for Sudan to investigate the performance of existing buildings if exposed to seismic loads. The frame was analyzed using the response spectrum method to calculate the seismic displacements and stresses.…”
Section: Objectives Of Studymentioning
confidence: 99%
“…The study makes use of the well-known civil engineering application STAAD-PRO to design multi-story buildings and calculate wind and seismic load. Also, they compare the results of calculations made manually and those made using STAAD-Pro when applying an earthquake load to a structure using the seismic coefficient A E. Hassaballa (2013) [7]"Seismic analysis of a multi-story RC frame in Khartoum city was analyzed under moderate earthquake loads as an application of seismic hazard and in accordance with the seismic provisions proposed for Sudan to investigate the performance of existing buildings if exposed to seismic loads. The frame was analyzed using the response spectrum method to calculate the seismic displacements and stresses.…”
Section: Objectives Of Studymentioning
confidence: 99%
“…It was discovered that buildings on medium soil face more base shear than those in hard soil. When a building is built on hard soil, it has less displacement and drifts than a building built on medium soil [11,18]. The current study was conducted in the area with medium soil to obtain better base shear.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because the equivalent static lateral force approach produces greater values of forces and moments, making construction uneconomical, the RSA method should be considered [16]. Another study found that the internal columns in all floor levels are the most affected by the compression forces caused by all load combinations [18]. For high-rise structures with vertical regularities, a dynamic analysis is required.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The primary objective of this study is to conduct an indepth examination of the implications associated with the installation of an external elevator within the context of a specific architectural setting: a typical 4-story reinforced concrete educational building situated at Kyungpook National University in Daegu, Republic of Korea. The methodology adopted for this analysis revolves around RSA (Response Spectrum Analysis), a robust analytical tool widely employed in seismic engineering to assess structural response under dynamic loading conditions [11][12][13][14][15][16][17]. By applying RSA techniques to SAP 2000, the study seeks to elucidate how the integration of an external elevator may influence the overall structural behavior and integrity of the existing RC frame.…”
Section: Introductionmentioning
confidence: 99%